COVID-19 or not COVID-19, that is the question. The role of screening criteria and point-of-care lung ultrasound in the triage decision-making process in an Emergency Department during the phase 2 of the COVID-19 Italian epidemic - Erika Poggiali; Davide Bastoni; Mariachiara Ferrari; Dario Moretto; Federico Buttafava; Pau Mateo Ramos; Valentina Burzio; Jolanda Petri; Andrea Magnacavallo; Andrea Vercelli (Emergency Care Journal, 2021)
In the COVID-19 era the real challenge for the Emergency Departments (ED) is to avoid the spread of the viral infection within the so called “clean area” of the emergency room and the hospital. Different protocols have been proposed and adopted in the EDs to quickly identify suspected COVID-19 patients and to correctly manage these patients, all based on clinical and epidemiological criteria. To the best of our knowledge, our pre-triage decisional making-process first integrates the pre-triage interview with pointof- care Lung Ultrasound (LUS) performed in the triage area. The aim of our study is to assess the sensitivity and specificity of our screening clinical and/or epidemiological criteria, and to investigate the role of LUS in the triage decision-making process during the “phase 2” of the COVID-19 Italian epidemic. Our study confirms the pivotal role of the triage in the decision-making process and the management of the entire ED, and it demonstrates that further studies are necessary to validate the role of LUS as tool to promptly identify COVID-19 patients, if combined with a correct pre-triage interview.